2016
DOI: 10.1111/boj.12438
|View full text |Cite
|
Sign up to set email alerts
|

Phytoliths as a tool for archaeobotanical, palaeobotanical and palaeoecological studies in Amazonian palms

Abstract: Phytoliths are silica bodies found in vascular plants, often diagnostic at the family level in angiosperms. They are especially abundant in palms (Arecaceae), occurring in all organs, with the highest concentrations in leaves. Phytoliths can remain in the soil for thousands or even millions of years, providing physical evidence of taxa in time and space. As such, they can be used to reconstruct ancient floras and landscapes, interpret events in plant evolution and document plant use by ancient peoples. In palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 30 publications
4
50
0
5
Order By: Relevance
“…All species and plant parts sampled produced abundant phytoliths, and contained one to four morphotypes ( Table 2). We identified several new subtypes of globular echinate and conical morphotypes, which were previously characterized by other researchers (e.g., Piperno, 2006;Morcote-Ríos et al, 2016; Figure 1). The newly identified subtypes were defined by the following characteristics:…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…All species and plant parts sampled produced abundant phytoliths, and contained one to four morphotypes ( Table 2). We identified several new subtypes of globular echinate and conical morphotypes, which were previously characterized by other researchers (e.g., Piperno, 2006;Morcote-Ríos et al, 2016; Figure 1). The newly identified subtypes were defined by the following characteristics:…”
Section: Resultssupporting
confidence: 62%
“…All samples were analyzed under a Leica Axiophot microscope with differential interference contrast (DIC) at 630x magnification using immersion oil. Categorization was based on Morcote-Ríos et al (2016), but new (sub)categories were created for newly identified morphotypes. A total of 300 phytoliths was counted per sample to quantify the relative abundances of morphotypes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used Piperno (2006) for identification of grass and arboreal phytoliths. For each palm species occurring in Amacayacu, we identified the phytolith morphotypes they produce using recently published reference guides (Huisman, Raczka, & McMichael, 2018;Morcote-Ríos, Bernal, & Raz, 2016) and the phytolith reference collection at the University of Amsterdam.…”
Section: Laboratory Analysismentioning
confidence: 99%